2003
DOI: 10.1074/jbc.m301090200
|View full text |Cite
|
Sign up to set email alerts
|

The CD44 Alternative v9 Exon Contains a Splicing Enhancer Responsive to the SR Proteins 9G8, ASF/SF2, and SRp20

Abstract: The CD44 gene alternative exons v8, v9, and v10 are frequently spliced as a block by epithelial cells. By transfecting minigenes containing only one of these alternative exons, we show that splicing of each of them is under cell type-specific control. By using minigenes carrying short block mutations within exons v8 and v9, we detected a candidate exon splicing enhancer in each of these exons. These candidates activated splicing in vitro of a heterologous transcript and are thus true exon splicing enhancers. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 43 publications
(59 reference statements)
1
37
0
2
Order By: Relevance
“…Galiana-Arnoux et al 22 have, however, recently demonstrated the presence within CD44 exon v9 of a splicing enhancer of approximately 30 nucleotides that binds the SR proteins 9G8, ASF/SF2 and SRp20, promoting inclusion of this particular exon. Similar splice enhancer elements have also been identified within several other alternatively spliced CD44 exons, most notably exon v5.…”
Section: Discussionmentioning
confidence: 99%
“…Galiana-Arnoux et al 22 have, however, recently demonstrated the presence within CD44 exon v9 of a splicing enhancer of approximately 30 nucleotides that binds the SR proteins 9G8, ASF/SF2 and SRp20, promoting inclusion of this particular exon. Similar splice enhancer elements have also been identified within several other alternatively spliced CD44 exons, most notably exon v5.…”
Section: Discussionmentioning
confidence: 99%
“…In other alternative splicing systems in which its action has been examined, 9G8 usually acts as a splicing activator (Cramer et al, 1999;Galiana-Arnoux et al, 2003;Li et al, 2000) and the sites it influences are also regulated by ASF/SF2 and/or SRp20. In our study, 9G8 acts as a strong splicing inhibitor and binds to an element which behaves as an intronic splicing silencer.…”
Section: G8 As a Regulator Of Other Alternatively Spliced Exonsmentioning
confidence: 99%
“…Therefore, these small SR proteins may have a role in CD44 splicing and metastasis, and they were also found to be up-regulated in a mouse mammary tumorigenesis model (55). 9G8 is one of the 30-kDa SR proteins, and a 9G8-responsive exonic splicing enhancer sequence was found in the v9 exon (56).…”
Section: Alternative Splicing Of Transmembrane Proteinsmentioning
confidence: 99%